Novel Pan-Pim Kinase Inhibitors With Imidazopyridazine and Thiazolidinedione Structure Exert Potent Antitumor Activities - Sawaguchi, Yuichi; Yamazaki, Ryuta; Nishiyama, Yukiko; Mae, Masayuki; Abe, Atsuhiro; Nishiyama, Hiroyuki; Nishisaka, Fukiko; Ibuki, Tatsuya; Sasai, Toshio; Matsuzaki, Takeshi (Frontiers in Pharmacology, 2021)
Pim kinases are overexpressed in various types of hematological malignancies and solid carcinomas, and promote cell proliferation and survival. Here in this study, we investigated the preclinical profile of novel pan-Pim kinase inhibitors with imidazopyridazine and thiazolidinedione structure. Imidazopyridazine-thiazolidinediones inhibited activities of Pim kinases with IC50 values of tens to hundreds nanomolar. With YPC-21440 and/or YPC-21817, which exhibited especially high inhibitory activities against Pim kinases, we investigated in vitro and in vivo activities of imidazopyridazine-thiazolidinediones. In silico analysis of binding mode of YPC-21440 and Pim kinases revealed that it directly bound to ATP-binding pockets of Pim kinases. In the kinase panel tested, YPC-21440 and YPC-21817 were highly specific to Pim kinases. These compounds exerted antiproliferative activities against various cancer cell lines derived from hematological malignancies and solid carcinomas. Furthermore, they suppressed phosphorylation of Pim kinase substrates, arrested cell cycle at the G1 phase, and induced apoptosis in cultured cancer cells. In tumor xenograft models, YPC-21440 methanesulfonate and YPC-21817 methanesulfonate exerted antitumor activities. Furthermore, pharmacodynamic analysis with a xenograft model suggested that YPC-21817 methanesulfonate inhibited Pim kinases in tumors. In conclusion, our data revealed that imidazopyridazine-thiazolidinediones are novel Pim kinases inhibitors, effective on various types of cancer cell lines both in vitro and in vivo.